Changes in lives of Kishori Supervisors due to employment in BRAC Education Programme - Khan, Md. Kaisar Ali; Hossain, Md. Altaf (BRAC Research and Evaluation Division (RED), 2019)
This study aimed at exploring changes that occurred in the lives of Kisohri supervisors (KS) due to employment in the BRAC Education Programme CBEP). Twenty-six KSs, 24 non-KSs, 36 of their guardians, 67 community people and 5 regional sectors specialists of six Team Offices of BEP were interviewed. Findings reveal that due to employment, the KSs were benefited economically - they were no longer dependent on their households, especially for their schooling, rather they often provided economic supports to their households. Their social status, mobility and social network increased significantly. Their employment contributed to their schooling but it created problem in attending the classes held in the afternoon because they had to visit reading centers in the afternoon. As they had to work six days a week, it might cause poor attainment in schools. The study further reveals that adolescents' employment in the BRAC programme helped change economic and social culture of tOheir families, lead taking greater participation in the household's economic decision making, access to financial and economic resources, facilitated greater social freedom of mobility and created new social networks. It also discouraged practice of early marriage. Finally, considering the economic and social benefits of the girls it can be concluded that more adolescent girls can be employed following existing selection criteria. At the same time, it is necessary to explore ways of retaining their level of educational attainment at the school level.